Odpowiedź :
Odpowiedź:
[tex]\begin{cases}\frac{x-2}{2}+y=1\ \ /*2\\\frac{x-2}{4}+2y=-1\ \ /*4\end{cases}\\\\\\\begin{cases}x-2+2y=2\\x-2+8y=-4\end{cases}\\\\\\\begin{cases}x+2y=2+2\\x+8y=-4+2\end{vcases}\\\\\\\begin{cases}x+2y=4\ \ /*(-1)\\x+8y=-2\end{cases}\\\\\\+\begin{cases}-x-2y=-4\\x+8y=-2\end{cases}\\---------\\6y=-6\ \ /:6\\y=-1\\\\\\x+2*(-1)=4\\\\x-2=4\\\\x=4+2\\\\x=6\\\\\begin{cases}x=6\\y=-1\end{cases}[/tex]
Odpowiedź:
[tex]\left \{ {{\frac{x-2}{2}+y =1/*2} \atop {\frac{x-2}{4}+2y=-1/*(-4)}} \right.[/tex]
[tex]\left \{ {{x-2+2y=2} \atop {-x+2-8y=4}} \right.[/tex]
[tex]\left \{ {{x+2y=4} \atop {-x-8y=2}} \right.[/tex]
---------------------
-6y=6/:(-6)
y=-1
[tex]\frac{x-2}{2}+(-1)=1/*2[/tex]
x-2-2=2
x=2+4
x=6
(x,y)=(6,-1)
Szczegółowe wyjaśnienie: